Patient and public involvement cultures and the perceived impact in the vulnerable context of palliative care: A qualitative study - Inge Melchior; Anouk van derHeijden; Esther Stoffers; Frits Suntjens; Albine Moser (Wiley, 2021)
Abstract Background Cultural values are crucial to the practice and impact of patient and public involvement (PPI) in research. Objective To understand different PPI cultures among research teams and the impacts of PPI associated with each culture type. Design A participatory action research design. Setting and participants The setting was 10 palliative care research projects. Seventeen patients and members of the public and 31 researchers participated. Intervention A programme consisting of four components: (1) training and coaching of patients and the public to prepare them for participation in research, (2) tailored coaching of the 10 research teams over 12‐18 months, (3) a community of practice, and (4) a qualitative evaluation. Results We identified three cultures types: relationship cultures, task cultures, and control cultures. We identified four areas of impact: the project aim became more relevant to the target audience, methodological reliability increased, the research products were better able to reach the public, and the awareness increased, associated with behavioural changes, among researchers regarding PPI. Discussion A relationship culture appears to be long‐lasting due to impacting the behaviours of the researchers during future projects. Different cultural types require different types of patients and researcher participants, assigned to different tasks. Conclusions Further research remains necessary to investigate the support required by researchers to enable relationship‐ and task‐oriented PPI cultures. Patient or public contribution Patient advocates and representatives contributed to our research team throughout the entire research process, as well as within the 10 implementation projects.